BEBERAPA ISSU STRATEGIS JANGKA PENDEK DI DAERAH DAN LANGKAH ANTISIPASINYA - Tri Widodo W. Utomo (Jurnal Borneo Administrator, 2005)
Following the commencement of democratic and decentralized era in Indonesia, both political and socio-economic climate has tented to be more dynamic in the grassroots level. ‘Change’ is the most prominent term found in local politics, covering three fundamental aspects, i.e. political, public administration, and constitutional law. Such changes bring about the conscience to recognize their implication and the needs to readjust the current system in line with the spirit of reform. This paper analyses five essential issues faced by local government and local people, i.e. direct election of Local Government Head, institutional arrangement, development planning system and documents, evaluation of inappropriate regional regulations, and perplexing issue on legal hierarchy. It also provides some recommendations could be taken in dealing with those issues.